2019
DOI: 10.3390/ijerph16030344
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Prediction of Motivational Climate in Handball Players’ Fear of Failure

Abstract: Sports can at times become a negative socializing agent for athletes. The objectives here were to analyse the relationship between motivational climates (involving coaches and peers) and fear of failure in players according to gender and sports experience, and also to control for the extent to which these motivational climates predict the different aversive causes of fear of failure. To this aim, a non-experimental, descriptive, and sectional design was used in which participants answered the Perceived Motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…The national federation, the regional federations, and the coaches of the different regional teams all granted permission prior to our data collecting after reading a letter explaining the objectives of the study and the way it would be carried out. Prior to the administration of the questionnaires to the participants, and in accordance with the ethical guidelines of the American Psychological Association (APA), they were presented with an informed consent form [15] for ethical compliance and data protection, ensuring the rigor of the investigation and the privacy of the information obtained. The consent obtained from the players and their parents or tutors was both written and informed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The national federation, the regional federations, and the coaches of the different regional teams all granted permission prior to our data collecting after reading a letter explaining the objectives of the study and the way it would be carried out. Prior to the administration of the questionnaires to the participants, and in accordance with the ethical guidelines of the American Psychological Association (APA), they were presented with an informed consent form [15] for ethical compliance and data protection, ensuring the rigor of the investigation and the privacy of the information obtained. The consent obtained from the players and their parents or tutors was both written and informed.…”
Section: Methodsmentioning
confidence: 99%
“…Another important aspect is that players who perceive a coach task-involving climate in their training see defeat as a learning factor, and believe that success is achieved with effort, as opposed to those who were subject to an ego climate, for whom ability and tricks are the main tools by which to succeed in sports [1,21]. Furthermore, coaches who promote a task-involving climate see mistakes as part of players' learning processes, a stance that is transmitted to their players, who thus feel lower levels of fear of failure, as recently shown by Gómez-López, Ruiz-Sánchez, and Granero-Gallegos [15] in a study with handball players. On the other hand, the literature has shown that athletes' perceptions of a master's climate are associated with low levels of anxiety [41,46,50,51].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existing literature indicates that a mix of personal, situational, and social factors influence antisocial behaviors in sport (see Kavussanu, 2019). Specifically, athletes’ antisocial behaviors have been linked to individual characteristics (Hodge and Gucciardi, 2015; Kavussanu, Stanger, and Ring, 2015; Rutten et al., 2011) and the sports setting (i.e., the culture of the team, including the interpersonal relationships between coaches and players) (Gómez‐López, Ruiz‐Sánchez, and Granero‐Gallegos, 2019; Ruiz et al., 2019). For example, Malete, Chow, and Feltz (2013) demonstrated that coaches' endorsement of cheating leads to antisocial behavior of players.…”
Section: Literature Reviewmentioning
confidence: 99%